Targeted therapy for cancer using pH-responsive nanocarrier systems - Manchun, S.; Dass, Crispin; Sriamornsak, P. (Elsevier, 2012)
Most of the conventional chemotherapeutic agents used against cancer have poor efficacy. An approach to improve the efficacy of cancer chemotherapy is the development of carrier systems that can be triggered to release the anticancer drug in response to extracellular or intracellular chemical stimuli. To this end, pH-responsive nanocarriers have been developed to target drugs either to the slightly acidic extracellular fluids of tumor tissue or, after endocytosis, to the endosomes or lysosomes within cancer cells. These systems can release the drug by specific processes after accumulation in tumor tissues via the enhanced permeability and retention (EPR) effect or they can release the drugs in endosomes or lysosomes by pH-controlled hydrolysis after they are taken up by the cell via the endocytic pathway. This strategy facilitates the specific delivery of the drug while reducing systemic side-effects with high potential for improving the efficacy of cancer chemotherapy.